The Efficacy of Jigsaw-Learning Model on Academic Performance of Polytechnic Students with Varied Learning Abilities in Kano, Nigeria - Ali m.suleiman; Bichi s.s; J.S Mari; M.A Lakpini (Comparative Education Society of Iran ( CESIR), 2018)
The Efficacy of jigsaw-learning model on students' academic performance in chemistry at the polytechnic level in Nigeria has not been not been adequately investigated. This study therefore investigates such effect by comparing the academic performance of higher ability, average ability and low ability students exposed to the jigsaw-learning model and those exposed to the traditional method. Two groups of students were randomly selected for the study. One group was exposed to the Jigsaw-learning model of cooperative learning (experimental group) while the other group was exposed to the traditional method (Control group). Variable investigated was effect of the strategy on academic performance of high ability, average and low abilities students. The data generated was subjected to Scheffs' test of multiple comparisons at p ≤0.05 level of significance. Result obtained revealed that: v  The use of jigsaw-learning model can be in tertiary institutes v  It has significant effect on the academic performance of students of all ability levels. v  It can be used to improve the performance of low abilities students v  It is a suitable method of teaching students of heterogeneous grouping. This paper therefore recommends that chemistry teachers in polytechnics and other tertiary institutes need to have a clear understanding of the abilities level of their students to enable them tailor their teaching to meet the students' learning abilities and need of their students.